Hi all,
I wanted to know what are the steps to simplify the following:
1/(x+1) - 1/(x-1)
= -2/(x^2-1)
= 2/(1-x^2)
as you can see the terms have been simplifyed but I don't know how it is done. I need help to show the steps please.
Thank you
1/(x+1) - 1/(x-1) .............combine fractions using the lcm as the product of the 2 denominators.
=...(x - 1) - (x + 1)
...----------------- ........do you know how to complete the numerator for this step?
......(x - 1)(x + 1)
=...x - 1 - x - 1
...--------------
.......(x^2 - 1)
=.........-2
......------------
........(x^2 - 1)
=...-1...................-2
....----.....x....------------ i'm essentially multiplying by 1 here so no change
.....-1..............(x^2 - 1)
=...........2
......------------
........(1 - x^2)